TRANSFER INFORMASI HARGA SAHAM-SAHAM YANG LISTING DI JAKARTA STOCK EXCHANGE DAN NEW YORK STOCK EXCHANG - Wardani, Heni Setia; Wahyudi, Sugeng; Waridin, Waridin (JURNAL BISNIS STRATEGI, 2001)
The stock price's information transfer between the stock exchanges which trading in dual listing stock will present information for the investor to evaluated the issuers prospect, because the information is a signal for the investor to make decision. When there is no obstacles against the information ditribution, the stock price's information transfer will work appropriately so that the information dissemination runs quickly. The distribution information here means thatb every investor receives the same information set. In fact, however, there were investor receiving information other than the others, so that thwe asymmetrical information generated., it was only some investors obtaining the suitable information. consequently the investor receiving this information could enjoy the ubnormal returns The rsearch utilized the listing stocks et the emerging and developed stock exchanges, because at present the investor tended to move their invesment strategy through the under-depeloved countries. in this research, the emerging stock exchange was jakarta stock exchange while the developed stock exchange was  new york stock exchange.This research intended to understand the movement direction of the stock price's information transfer and to detect the movement response of the stock price's information transfer from New York Stock Exchange to Jakarta Stock Exchange and/or on the contrary from Jakarta Stock Exchange to New York Stock Exchange.In reach of this study census was applied as the reserach method because all population members became the research  objects. The relevant population  comprised all issuers performing the listing at  New York Stock Exchange and Jakarta Stock Exchange. The secondary data involving daily data of the stock price, exchanges rates, Jakarta Composite Index , and Dow Jones Industrial index stemmed From Bisnis Indonesia Daily News during 1999 was used within this research.  The analysis tool used in this was ordinary linear regression to know the movement direction and response of stock price's information transfers.Based on this research it was found that the stock price's information transfer running to two directions, from New York Stock Exchange to Jakarta Stock Exchange even so from Jakarta Stock Exchange to New York Stock Exchange and the stronger impact moved from Jakarta Stock Exchange to New York Stock Exchange.